Revolutionizing tropical fruits preservation: Emerging edible coating technologies - Olunusi, Samuel Olugbenga; Nor Hanuni, Ramli; Fatmawati, Adam; Ahmad Fahmi, Ismail; Okwuwa, Chigozie Charity (Elsevier Ltd, 2024)
Tropical fruits, predominantly cultivated in Southeast Asia, are esteemed for their nutritional richness, distinctive taste, aroma, and visual appeal when consumed fresh. However, postharvest challenges have led to substantial global wastage, nearly 50 %. The advent of edible biopolymeric nanoparticles presents a novel solution to preserve the fruits' overall freshness. These nanoparticles, being edible, readily available, biodegradable, antimicrobial, antioxidant, Generally Recognized As Safe (GRAS), and non-toxic, are commonly prepared via ionic gelation owing to the method's physical crosslinking, simplicity, and affordability. The resulting biopolymeric nanoparticles, with or without additives, can be employed in basic formulations or as composite blends with other materials. This study aims to review the capabilities of biopolymeric nanoparticles in enhancing the physical and sensory aspects of tropical fruits, inhibiting microbial growth, and prolonging shelf life. Material selection for formulation is crucial, considering coating materials, the fruit's epidermal properties, internal and external factors. A variety of application techniques are covered such as spraying, and layer-by-layer among others, including their advantages, and disadvantages. Finally, the study addresses safety measures, legislation, current challenges, and industrial perspectives concerning fruit edible coating films.